Dissecting Endoplasmic Reticulum Unfolded Protein Response (UPRER) in Managing Clandestine Modus Operandi of Alzheimer’s Disease - Rahman, Safikur; Archana, Ayyagari; Jan, Arif Tasleem; Minakshi, Rinki (Frontiers in Aging Neuroscience, 2018)
Alzheimer’s disease (AD), a neurodegenerative disorder, is most common cause of dementia witnessed among aged people. The pathophysiology of AD develops as a consequence of neurofibrillary tangle formation which consists of hyperphosphorylated microtubule associated tau protein and senile plaques of amyloid-β (Aβ) peptide in specific brain regions that result in synaptic loss and neuronal death. The feeble buffering capacity of endoplasmic reticulum (ER) proteostasis in AD is evident through alteration in unfolded protein response (UPR), where UPR markers express invariably in AD patient’s brain samples. Aging weakens UPRER causing neuropathology and memory loss in AD. This review highlights molecular signatures of UPRER and its key molecular alliance that are affected in aging leading to the development of intriguing neuropathologies in AD. We present a summary of recent studies reporting usage of small molecules as inhibitors or activators of UPRER sensors/effectors in AD that showcase avenues for therapeutic interventions.